The effect of local culture of naposo nauli bulung using a peer educator approach on adolescent sexual behavior - Siregar, Nurelilasari; Pebrianthy, Lola; Sagala, Nanda Suryani (Science Midwifery, 2024)
Sexual behavior is a major problem associated with juvenile delinquency cases. Sex remains a taboo topic in the general Indonesian public, social stigma about sexuality and sex outside marriage in Isndonesia causes the prevalence of premarital sex to go unreported substantially. The purpose of this study was to identify the influence of Local Culture Naposo Nauli Bulung with a peer educator approach on adolescent sexual behavior. The study was an experimental quasy with a one group pre-test post-test approach. The study was conducted in Padangsidimpuan City from July to October 2023, the population in this study was all adolescents in Padangsidimpuan City and the research sample was 180 respondents taken from 6 villages in 6 sub-districts of Padangsidempuan City that had active Naposo Nauli Bulung. The data analysis used is the Wilcoxon test. The results showed the influence of the peer educator method based on Naposo Nauli Bulung on improving adolescent sexual behavior with a p value of 0.000 (p < 0.05). The conclusion of this study is that there is an influence of peer educators based on Naposo Nauli Bulung in improving adolescent sexual behavior so that this method can be recommended as a method in improving adolescent education related to sexual behavior